An ultra-compact blackbody using electrophoretic deposited carbon nanotube films. Issue 7 (17th January 2018) - Lin, Albert; Yang, Chien-Chih; Parashar, Parag; Lin, Chien-Yung; Jian, Ding Rung; Huang, Wei-Ming; Huang, Yi-Wen; Fu, Sze Ming; Zhong, Yan Kai; Tseng, Tseung Yuen
Abstract : Electrophoretic-deposited carbon nanotubes (EPD-CNTs) possess decent optical properties and low-cost processing and thus can be used as an ideal black body with compact dimension. Abstract : Carbon nanotubes (CNTs) possesses decent optical properties and thus can be considered as a candidate for perfect absorbers due to their close-to-air refractive index and minimal extinction. However, weak absorption in porous materials, due to the low extinction coefficients, requires an inevitably thick absorption layer (∼100 μm) for the perfect opaque absorbers. Thus, the requirement of large thicknesses of CNTs prohibits them from being used as miniaturized integrated photonic devices. Here, we propose an electrophoretic deposited (EPD) CNT resonant cavity structure on tantalum (Ta) to enhance optical absorption. Efficient random light scattering along with the resonant cavity structure using Ti/SiO2 stacking enhances the absorption in our proposed EPD-CNT film while maintaining the total device thickness to <1 μm. The experiment results reveal that the absorption band covers the entire UV-VIS-NIR spectrum ( λ = 0.3–2.6 μm), using resonant-cavity EPD-CNT design. The EPD deposition process is done at relatively low temperature < 120 °C. We believe that this proposal is very promising for sensing, antenna, and thermophotovoltaics (TPV), in terms of bandwidth, compactness and cost.